THE EFFECT OF THE CONSTRUCTED WETLAND SUBSURFACE MODEL USING TWO SPECIES OF Epipremnum aureum AND Canna indica IN REDUCE COD IN LAUNDRY WASTE - Hiskia Riopratama; Haryati Bawole Sutanto; Guruh Prihatmo (Universitas Medan Area, 2023)
Pollution of aquatic ecosystems is mostly caused by human activities such as the laundry industry in urban areas, where often the disposal of laundry waste that is discharged directly without proper management triggers environmental pollution. There are two compounds in laundry waste that are difficult to decompose naturally in water, which can trigger environmental pollution in river ecosystems, namely sodium dodecyl benzene sulfonate (NaDBS) and sodium tripolyphosphate (STTP). Therefore, it is necessary to carry out integrated treatment measures, one of which is the Subsurface Flow Constructed Wetland model. This research aims to see the level of effectiveness of the subsurface Flow constructed wetlands model using two types of plants, namely Epipremnum aureum and Canna indica in reducing the laundry waste parameters such as Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and Detergent. This research was carried out experimentally by comparing the output of the reactor processing between the inlet and outlet. Based on this research, it can be concluded that the level of effectiveness of laundry waste treatment in the subsurface flow constructed wetland system model uses two types of plants, namely Epipremnum aureum and Canna indica can reduce the concentration of test parameters, namely COD by 76.4%, TSS by 66.2%, and Detergent by 80.9%.